1995
DOI: 10.1073/pnas.92.5.1510
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of SNAP-25 protein isoforms during divergent vesicle fusion events of neural development.

Abstract: The presynaptic plasma membrane protein SNAP-25 (synaptosome-associated protein of 25 kDa) has been implicated as one of several neural-specific components that direct constitutive fusion mechanisms to the regulated vesicle trafficking and exocytosis of neurotransmitter release.There exist two alternatively spliced isoforms of a and b, which differ in a putative membrane-interacting domain. We show that these two isoforms have distinct quantitative and anatomical patterns of expression during brain develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
236
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(251 citation statements)
references
References 44 publications
15
236
0
Order By: Relevance
“…alternative splicing between tandem exon 5. 36 This results in a developmental switch between 1 and 3 weeks of age from expression of predominantly SNAP25a to SNAP25b transcripts that ultimately constitute more than 80% of SNAP25 mRNA in mouse adult brain. These two isoforms diverge only for nine amino acids in a domain involved in membrane association and disassembly, after exocytosis, of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex.…”
Section: Discussionmentioning
confidence: 99%
“…alternative splicing between tandem exon 5. 36 This results in a developmental switch between 1 and 3 weeks of age from expression of predominantly SNAP25a to SNAP25b transcripts that ultimately constitute more than 80% of SNAP25 mRNA in mouse adult brain. These two isoforms diverge only for nine amino acids in a domain involved in membrane association and disassembly, after exocytosis, of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular interest when studying the SNARE complex proteins, as it has been shown that different combinations of SNARE protein isoforms interact with dissimilar affinities and are differentially distributed in defined areas of the central nervous system, suggesting specialized functions of these isoforms (29). Other SNARE protein isoforms such as SNAP-25A and -25B have very different expression during embryonic and early postnatal development: SNAP-25A is the predominant species during embryonic and early postnatal development, whereas SNAP-25B transcripts increase dramatically after the first postnatal week to become the majority of SNAP-25 mRNA in adult brain (38,39). Other studies have shown that different SNARE protein isoforms could have specialized roles in the neurosecretory process (40).…”
Section: Discussionmentioning
confidence: 99%
“…SNARE proteins synaptobrevin, SNAP-25 and syntaxin 1A are expressed in early development in hippocampal cultures 144,145 though more dominant isoforms may exist. For example, cleavage of the mature v-SNARE isoform synaptobrevin by tetanus toxin, completely blocks neurotransmission in mature terminals 146 whereas new synapses express a tetanus toxin-resistant isoform of synaptobrevin 145 In rat brain, SNAP-25 expression switches from SNAP-25a during development, to SNAP-25b in mature terminals 147,148 which is purported to be controlled by developmental patterns of electrical activity (i.e., calcium influx). 149 Finally, a splice isoform of syntaxin 1A, termed syntaxin 1C, has been reported.…”
Section: Regulation By Alternate Splicingmentioning
confidence: 99%